Establishing Quantitative Systems for Evaluating and Enhancing Noncanonical Amino Acid Incorporation in Yeast - Potts, Kelly. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Chemical and Biological Engineering.; Advisor: James Van Deventer.; Committee: Catherine Freudenreich, and Nikhil Nair.; Keywords: Chemical engineering, Biochemistry, and Biology.